The effect of synthetic cannabinoid ADB-FUBINACA on primary neuronal cultures ß-galactosidase activity: preliminary findings - Roque-Bravo, Rita (2024)
Background: ADB-FUBINACA (ADB-FUB) is a synthetic cannabinoid (SC) that has gained popularity among users as a new psychoactive substance. This stems from SC's pharmacological similarity to the active principle of cannabis, D9-tetrahydrocannabinol (THC). However, unlike THC, SCs demonstrate full agonism of cannabinoid receptors 1 and 2 [1]. Recent scientific developments have shown that cannabis use may aggravate ageing-related parameters [2,3]. Moreover, a study using human fibroblasts revealed that 1 µM THC (2h-long exposure, for 15 days) can increase ß-galactosidase activity [3], which serves as a first-line marker for cellular senescence. Objective: This study was designed to investigate whether these biologically-relevant concentrations could accelerate neuronal ageing. Methods: PHC were isolated from Wistar rat day 18-19 embryos and cultured for up to 21 days-in-vitro (DIV). Exposure to 1 pM, 1 nM and 1 µM ADB-FUB (concentrations previously shown to be non-cytotoxic to PHC) started either on DIV3 or DIV7 and was maintained up to 21 DIV. At that final timepoint, ß-galactosidase activity was evaluated. DMSO at 0.02% was employed as solvent control. Results: Under these experimental conditions, PHC exposed to 1 nM and 1 µM ADB-FUB in the DIV3-21 protocol had lower ß-galactosidase activity when compared to control conditions (p<0.05, 1 nM; p<0.001, 1 µM). No statistically significant results were registered for PHC under the DIV7-21 exposure protocol. Conclusions: These findings are, to the best of our knowledge, the first evidence of a potential “anti-ageing” effect of ADB-FUB. Evaluation of other senescence-related endpoints will follow. Moreover, experiments using another in vitro neuronal model (human neuroblastoma cell line SH-SY5Y) are underway to compare the effects of the same drug in different models and further substantiate conclusions on ADB-FUB’s effect.